2019
DOI: 10.1002/ecy.2905
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence for spatial resource partitioning across temperate grassland biodiversity experiments

Abstract: Locally, plant species richness supports many ecosystem functions. Yet, the mechanisms driving these often-positive biodiversity-ecosystem functioning relationships are not well understood. Spatial resource partitioning across vertical resource gradients is one of the main hypothesized causes for enhanced ecosystem functioning in more biodiverse grasslands. Spatial resource partitioning occurs if species differ in where they acquire resources and can happen both above-and belowground. However, studies investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 86 publications
1
53
1
Order By: Relevance
“…If intraspecific competition for soil moisture outweighs interspecific competition during these dry periods (e.g., niche complementarity effects, HilleRisLambers et al 2012), individual species may experience alleviation of intense intraspecific competition when growing in higher-diversity plots. Although we cannot rule this out as a contributing mechanism, a recent meta-analysis by Barry et al (2020) found that spatial resource partitioning for belowground resources is quite rare in 21 experimental manipulations of grassland biodiversity around the world. Although competition for soil moisture is inevitably occurring, it is likely paired with well-known aboveground effects of diversity on evaporative demand.…”
Section: Facilitation and Alleviation Of Competition In Higherdiversimentioning
confidence: 89%
See 1 more Smart Citation
“…If intraspecific competition for soil moisture outweighs interspecific competition during these dry periods (e.g., niche complementarity effects, HilleRisLambers et al 2012), individual species may experience alleviation of intense intraspecific competition when growing in higher-diversity plots. Although we cannot rule this out as a contributing mechanism, a recent meta-analysis by Barry et al (2020) found that spatial resource partitioning for belowground resources is quite rare in 21 experimental manipulations of grassland biodiversity around the world. Although competition for soil moisture is inevitably occurring, it is likely paired with well-known aboveground effects of diversity on evaporative demand.…”
Section: Facilitation and Alleviation Of Competition In Higherdiversimentioning
confidence: 89%
“…Furthermore, resource partitioning theory suggests that intraspecific competition should be greater than interspecific competition for many species (HilleRisLambers et al 2012). Although conspecific neighbors likely compete for resources in overlapping ways, heterospecific neighbors may have complementary root distributions (but see Barry et al 2020), alternative physiological strategies to combat water stress (Fotelli et al 2000), or alternative energy allocation patterns that reduce water loss aboveground (e.g., lower specific leaf area of leaves). If intraspecific competition outweighs interspecific competition, this could buffer species from strong competition for soil water during drought.…”
Section: Introductionmentioning
confidence: 99%
“…2019a), which can have varying implications for measures of ecosystem function above and below ground (Barry et al . 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing and increasing exploitation of terrestrial and marine resources, direct exploitation of organisms, as well as climate change, are reducing plant diversity (IPBES, 2019), which negatively impacts a diverse array of ecological functions that are critical for sustaining humanity (Cardinale et al., 2012). In terrestrial ecosystems, increased aboveground productivity with plant species diversity is accompanied by greater fine root biomass and productivity (Barry et al., 2020; Ma & Chen, 2016; Zhang et al., 2012). This suggests that plant species mixtures require additional soil resources (water and nutrients) and/or increased resource use efficiency to support higher above‐ and belowground productivity, in contrast to corresponding monocultures.…”
Section: Introductionmentioning
confidence: 99%